Foreign Ownership and Transferring of Gender Norms - Daniel Halvarsson; Olga Lark; Patrik Gustavsson Tingvall (Lund University, School of Economics and Management, Department of Economics, 2022)
In this paper, we study foreign ownership as a vehicle for transferring gender norms across international borders. Specifically, we analyze how the wage differential between men and women in Swedish firms is affected by the degree of gender inequality in the home country of foreign investors. The results suggest that gender norms of the home country matter—the gender wage gap in foreign-owned subsidiaries appears to increase with the degree of gender inequality prevailing in the investors' home market. This finding is identified from within job-spell variation in wages and proves robust across a series of specifications.
Keywords: F66; J16; J31; 330; Foreign ownership; Gender inequality; Gender wage gap; Internationalization; Gender norms